Teaching English in Higher Educational Institutions Using Total Physical Response Principles - Shorobura, Inna; Vornyk, Mariya (Journal of Education, Health and Sport, 2025)
The article explores the application of Total Physical Response (TPR) principles in teaching English in higher educational institutions. The study focuses on modern pedagogical perspectives on TPR and its relevance for adult learners in university contexts. Although traditionally associated with teaching young learners, TPR is reconsidered as an effective approach for enhancing vocabulary acquisition, grammatical competence, learner engagement, and motivation in higher education. The article analyzes recent research on kinesthetic learning, embodied cognition, and communicative language teaching, demonstrating that physical involvement supports deeper language processing and retention. Practical strategies for implementing TPR principles in vocabulary and grammar instruction at the tertiary level are proposed. The findings confirm that TPR contributes to creating an interactive, student-centered, and low-anxiety learning environment, which is essential for developing communicative competence among university students.